Evaluation and reevaluation - William Edridge (South African Medical Association, 2014)
Recommended treatments for a variety of problems are introduced with good intentions after evaluation, and sometimes, after unimagined complications or complications of unimagined extent, later withdrawn. All treatments must be re-evaluated to assess whether their efficacy and safety can be sustained, or whether complications or failure will reach the levels at which modifications or alternative therapies will be explored.